Binge drinking and blood pressure: cross-sectional results of the HAPIEE study - Pajak, Andrzej; Szafraniec, Krystyna; Kubinova, Ruzena; Malyutina, Sofia; Peasey, Anne; Pikhart, Hynek; Nikitin, Yuri; Marmot, Michael; Bobak, Martin (PLoS One, 2013)
OBJECTIVES: To investigate whether binge drinking pattern influences blood pressure independently from drinking volume or whether it modifies the effect of volume of drinking. METHODS: We used cross-sectional data from population samples of 7559 men and 7471 women aged 45-69 years in 2002-05, not on antihypertensive medication, from Russia, Poland and Czech Republic. Annual alcohol intake, drinking frequency and binge drinking (≥ 100 g in men and ≥ 60 g in women in one session at least once a month) were estimated from graduated frequency questionnaire. Blood pressure was analysed as continuous variables (systolic and diastolic pressure) and a binary outcome (≥ 140/90 mm Hg). RESULTS: In men, annual alcohol intake and drinking frequency were strongly associated with blood pressure. The odds ratio of high blood pressure for binge drinking in men was 1.62 (95% CI 1.45-1.82) after controlling for age, country, body mass index, education and smoking; additional adjustment for annual alcohol intake reduced it to 1.20 (1.03-1.39). In women, the fully adjusted odds ratio of high blood pressure for binge drinking was 1.31 (1.05-1.63). Binge drinking did not modify the effect of annual alcohol intake. Consuming alcohol as wine, beer or spirits had similar effects. CONCLUSIONS: The results suggest that the independent long-term effect of binge drinking was modest, that binge drinking did not modify the effect of alcohol intake, and that different alcoholic beverages had similar effects on blood pressure.
Keywords: Binge Drinking; Odds Ratio; odds ratio; hypertenze; Female; Prevalence; systola; Diastole; ženské pohlaví; průřezové studie; Beverages; lidé; nápoje; nárazové pití alkoholu; krevní tlak; Humans; prevalence; Cross-Sectional Studies; Hypertension; Male; Aged; Czech Republic; Russia; Systole; diastola; Česká republika; lidé středního věku; senioři; mužské pohlaví; Poland; Blood Pressure; Middle Aged; Rusko; Polsko